Analisis Tingkat Kemiskinan Petani Tanaman Pangan di Desa Penyangga Kawasan Ekonomi Khusus Mandalika, NTB: Analysis of Poverty Levels of Food Crops Farmers in The Buffer Village of Mandalika Special Economic Zone, NTB - Ayu, Candra; Wuryantoro; Wulandari, Febriana Tri; Dewi Mandalika, Eka Nurminda (HUTAN TROPIKA, 2024)
The Mandalika Special Economic Zone was developed to encourage regional economic growth, especially Central Lombok Regency, where most of the area is dry land. However, the Human Development Index for this area remains the second lowest in NTB and the poor population remains high, mainly due to low productivity and income from dry land farming. The largest dry land is in Pujut District which is the seat of the Mandalika SEZ. This research aims to analyze the poverty level of food crop farmers in the buffer villages of Mandalika SEZ. The type of research was descriptive, data collection using survey techniques in Sengkol Village, Rembitan Village and Sukadana Village and 45 farmer respondents. The results of the study revealed that the per capita income of food crop farmers was IDR 4,592,057.14/capita/year; equivalent to 352.26 kg of rice/capita/year or equivalent to US$ 0.79/capita/day so that it is classified as poor based on the Sajogyo Poverty Criteria and the World Bank Criteria. The per capita income level is only 15% of the Central Lombok Regency Minimum Wage Standards .